Conjunctive reward–place coding properties of dorsal distal CA1 hippocampus cells - Xiao, Zhuocheng; Lin, Kevin; Fellous, Jean-Marc (Biological cybernetics, 2020)
Autonomous motivated spatial navigation in animals or robots requires the association between spatial location and value. Hippocampal place cells are involved in goal-directed spatial navigation and the consolidation of spatial memories. Recently, Gauthier and Tank (Neuron 99(1):179–193, 2018. https://doi.org/10.1016/j.neuron.2018.06.008 ) have identified a subpopulation of hippocampal cells selectively activated in relation to rewarded goals. However, the relationship between these cells’ spiking activity and goal representation remains elusive. We analyzed data from experiments in which rats underwent five consecutive tasks in which reward locations and spatial context were manipulated. We found CA1 populations with properties continuously ranging from place cells to reward cells. Specifically, we found typical place cells insensitive to reward locations, reward cells that only fired at correct rewarded feeders in each task regardless of context, and “hybrid cells” that responded to spatial locations and change of reward locations. Reward cells responded mostly to the reward delivery rather than to its expectation. In addition, we found a small group of neurons that transitioned between place and reward cells properties within the 5-task session. We conclude that some pyramidal cells (if not all) integrate both spatial and reward inputs to various degrees. These results provide insights into the integrative coding properties of CA1 pyramidal cells, focusing on their abilities to carry both spatial and reward information in a mixed and plastic manner. This conjunctive coding property prompts a re-thinking of current computational models of spatial navigation in which hippocampal spatial and subcortical value representations are independent.